2006
DOI: 10.1590/s0100-879x2006000600009
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral markers of oxidative stress in chronic mercuric chloride intoxication

Abstract: The present study was designed to evaluate the time course changes in peripheral markers of oxidative stress in a chronic HgCl 2 intoxication model. Twenty male adult Wistar rats were treated subcutaneously daily for 30 days and divided into two groups of 10 animals each: Hg, which received HgCl 2 (0.16 mg kg -1 day -1 ), and control, receiving the same volume of saline solution. Blood was collected at the first, second and fourth weeks of Hg administration to evaluate lipid peroxidation (LPO), total radical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
(16 reference statements)
3
12
0
Order By: Relevance
“…It has been shown that heavy metals such as mercury, lead and thallium reduce antioxidative enzymes such as SOD, CAT, GLU and Lipid peroxidase (LPO) (Woodside et al, 2005;Farina et al, 2013). The present study agrees with the findings that showed that oxidative stress was an important component of the mechanism of toxicity by heavy metals (Gutierrez et al, 2006). It has been shown that acute exposure to mercury increases LPO and decreases SOD levels in experimental animals.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that heavy metals such as mercury, lead and thallium reduce antioxidative enzymes such as SOD, CAT, GLU and Lipid peroxidase (LPO) (Woodside et al, 2005;Farina et al, 2013). The present study agrees with the findings that showed that oxidative stress was an important component of the mechanism of toxicity by heavy metals (Gutierrez et al, 2006). It has been shown that acute exposure to mercury increases LPO and decreases SOD levels in experimental animals.…”
Section: Discussionsupporting
confidence: 92%
“…These changes might mean that antioxidant defenses are effectively related to endothelial venous function improvement induced by dialysis, because patients with major improvement in endothelial function presented the lower TRAP reduction. Oxidative stress was measured through a very sensitive method that involves chemiluminescence, allowing high precision determinations with small amounts of sample (23). One limitation of our study was that we did not measure systemic inflammatory mediators that could be related to chronic renal failure itself and also to the hemodialysis session (24), since changes in these mediators could partially explain the endothelial function improvement.…”
Section: Discussionmentioning
confidence: 99%
“…They increase oxidative stress and decrease intracellular levels of glutathione in vitro. Chronic administration of HgCl 2 to rats caused an imbalance in oxidative stress and a significant decrease in the animal's body weight compared with control [6].…”
Section: Introductionmentioning
confidence: 87%